L'alta atmosfera e una nuova proprieta del plasma (ionosfera) - M. CUTOLO (Annals of Geophysics, 1964)
We give first some news on the constitution of the atmosphere and ionosphere (Fig. 1), and on the variation of the temperature in relation with the height (Fig. 2) as by the most recent knowledges.